Transcriptome Profiling Reveals Pro-Inflammatory Cytokines and Matrix Metalloproteinase Activation in Zika Virus Infected Human Umbilical Vein Endothelial Cells - Khaiboullina, Svetlana; Uppal, Timsy; Kletenkov, Konstatin; St. Jeor, Stephen Charles; Garanina, Ekaterina; Rizvanov, Albert; Verma, Subhash C. (Frontiers in Pharmacology, 2019)
The deformities in the newborns infected with Zika virus (ZIKV) present a new potential public health threat to the world-wide community. Although ZIKV infection is mainly asymptomatic in healthy adults, infection during pregnancy can cause microcephaly and other severe brain defects and potentially death of the fetus. The detailed mechanism of ZIKV-associated damage is still largely unknown; however, it is apparent that the virus crosses the placental barrier to reach the fetus. Endothelial cells are the key structural component of the placental barrier. Endothelium integrity as semi-permeable barrier is essential to control the molecules and leukocytes trafficking across the placenta. Damaged endothelium or disruption of adherens junctions could compromise endothelial barrier integrity causing leakage and inflammation. Endothelial cells are often targeted by viruses, including the members of the Flaviviridae family such as Dengue virus (DENV) and West Nile Virus (WNV); however, little is known about the effects of ZIKV infection of endothelial cell functions. Our transcriptomic data have demonstrated that large number of cytokines is affected in ZIKV infected endothelial cells where significant change in 13 and 11 cytokines were identified in cells infected with PRVABC59 and IBH30656 ZIKV strains, respectively. Importantly, these cytokines include chemokines attracting mononuclear leukocytes (monocytes and lymphocytes) as well as neutrophils. Additionally, changes in matrix metalloproteases (MMPs) were detected in ZIKV infected cells. Furthermore, we, for the first time, show that ZIKV infection of human umbilical vein endothelial cells (HUVECs) increases endothelial permeability. We reason that increased endothelial permeability could be due to apoptosis of endothelial cells caused by caspase-8 activation in ZIKV-infected cells.